2013
DOI: 10.1016/j.mineng.2012.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Kaolinite and hematite flotation separation using etheramine and ammonium quaternary salts

Abstract: a b s t r a c tClay minerals are widespread in various types of mineral deposits. When present, they contribute to the high content of certain parameters such as silica, aluminium, and magnesium. This study aimed to find selectivity windows to separate hematite from a clay mineral (kaolinite) to allow reduction of the levels of silica and alumina in iron ore. The collectors used were: etheramine Flotigam EDA (EDA) and the ammonium quaternary salts: dodecyltrimethylammonium bromide (DTAB) and Tomamine Q-14-2 PG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Quaternary ammonium salts have been used in flotation. Rodrigues (2013) achieved separation of kaolinite from hematite using dodecyltrimethylammonium bromide as the collector in the pH range 4-10. Wang and Ren (2005) used a combination of cetyltrimethylammonium bromide and dodecylamine chloride as the collector and quebracho as a depressant to separate quartz from iron minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Quaternary ammonium salts have been used in flotation. Rodrigues (2013) achieved separation of kaolinite from hematite using dodecyltrimethylammonium bromide as the collector in the pH range 4-10. Wang and Ren (2005) used a combination of cetyltrimethylammonium bromide and dodecylamine chloride as the collector and quebracho as a depressant to separate quartz from iron minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed, dodecylamine (DDA) was the effective collector for flotation of both kaolinite and quartz [10]. In this part, flotation of kaolinite by DDA in the presence of aluminum chloride as quartz depressant was evaluated.…”
Section: Effect Of Ph On With Dda Collectormentioning
confidence: 99%
“…However, the time required for kaolinite flotation was 5-10 times longer that for the quartz flotation, depending on the type of collector [10].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the field of mineral processing, there are also intense investigations on flotation of quartz from iron ore using quaternary ammonium salts collectors [26]. However, there are almost no reports about the applications of quaternary phosphonium salts as collectors in iron ore beneficiation, and some attempts have been made in our previous work [27].…”
Section: Introductionmentioning
confidence: 99%